The art of colour the history of art in 39 pigments - Grovier, Kelly 1968- (Thames & Hudson, 2023)
Did you know that the ultramarine that shimmers at the centre of Vermeer's Milkmaid connects that masterpiece with 6th-century Zoroastrian paintings found on the walls of cave temples in Bamiyan, Afghanistan - Or that the surging waves that crest and curl in Hokusai's perilous Great Wave off Kanagawa owe their absorbing blue lustre to an alchemist who was born in Frankenstein's Castle in 1673? And were the Pre-Raphaelites really obsessed with a murky brown hue derived from the pulverized remains of ancient mummies? (Spoiler: they were.) Invented by prehistoric cave-dwellers and medieval conjurers, cunning conmen and savvy scientists, the colours of art tell a riveting tale all their own. Over ten scintillating chapters, acclaimed author Kelly Grovier helps bring that tale vividly to life, revealing the astonishing backstories of the pigments that define the greatest works in the history of art. Interwoven between these chapters is a series of features focusing on key moments in the evolution of colour theory - from the revelations of the Enlightenment to the radicalism of the Bauhaus - while reproductions of carefully selected artworks help illuminate the narrative's twists and turns. The history of colour is an epic saga of human ingenuity and insatiable desire. Read this book and you will never look at a work of art in quite the same way.
Keywords: Farbe; Pigment; Kunst